Case Report: First occurrence of Lymphocystis disease virus 3 (LCDV-Sa) in Wild Marine Fish in Tunisia - Nadia Cherif; Fatma Amdouni; Kaouther Maatoug; Sami Zaafran (Annals of Marine Science - Peertechz Publications, 2020)
The results of the present study describe the molecular identification of Lymphocystis Disease Viral partial genome (LCDV-Sa) and histopathology in skin nodules and internal organs of Tunisian gilthead sea bream (Sparus aurata). The report supports as well as the existence of multiple reservoirs of LCDV within wild fish species caught near the cage facility; delivering a list of possible vector species susceptible to transmit the disease to farmed sea bream. Histology sections revealed irregular nucleus with basophilic cytoplasmic inclusions. In addition, to the best of our knowledge, molecular results added new viral reservoirs to the list of susceptible fish species described worlwide, including Sardinella aurita, Sardina pilchardus, Trachurus trachurus, Sarpa salpa, Diplodus vulgaris, Diplodus puntazzo, Liza aurata, Sparus aurata, Diplodus anularis, and Spicara maena. The virus detection was not correlated with neither the fish species nor the sampling temperature which varied between 15°C and 25°C. Partial sequence analysis of the MCP gene indicated that the newly identified LCDV strains were clustered within genotype VII and shared 96-100% of sequence identity with previously identified Tunisian LCDV sequences from farmed sea bream.